Xpert MTB/RIF Ultra and mycobacterial culture in routine clinical practice at a Tertiary Paediatric Hospital - Enimil, Anthony Kwame (Department of Paediatrics and Child Health, 2022)
Introduction World Health Organization approved the use of Xpert MTB/RIF Ultra (Ultra) in children due to quick turn-around time, improved yield over smear microscopy, and ability to detect rifampicin resistance despite culture being the “gold standard”. This study reviewed published literature on current childhood tuberculosis diagnostic modalities. It also retrospectively compared demographic, clinical, and radiological features of children with confirmed and unconfirmed PTB, reviewed criteria for microbiologically unconfirmed PTB, and assessed incremental microbiological yield on second and third Ultra and/or mycobacterial culture results in routine clinical care at a tertiary paediatric hospital. Method For the review on childhood TB diagnostic modalities, PubMed was searched using Boolean terms OR/AND between childhood tuberculosis and words such as diagnosis, polymerase chain reaction, molecular, histology, imaging, and cultures. All abstracts were read after which selected articles that met the objectives of the thesis were fully reviewed and referenced appropriately. The retrospective study was conducted in children (0 to 13 years) treated for Pulmonary TB (PTB) between 1 February 2018 and 31 January 2019 and who had at least one respiratory specimen investigated by Ultra and/or mycobacterial culture before TB treatment was commenced. Relevant demographic, clinical information, tuberculin skin test results and laboratory results were abstracted from paper-based medical records and electronic database. Baseline chest radiographic findings were obtained from the radiology digital imaging database. All data was entered anonymously into a Microsoft Excel spreadsheet and exported to R-statistical software for statistical analysis. Descriptive and inferential statistics were used in the analysis. Incremental yield of Ultra and/or mycobacterial cultures on sequential respiratory specimens was determined. Results Ultra is an important diagnostic method for confirming TB in children even though mycobacterial culture, molecular, and histology tests are also available. Other modalities such as imaging and immunologic tests support the diagnosis of microbiologically unconfirmed TB. 174 children with PTB ± EPTB were included in the retrospective study. The median age was 2.5 years. Tuberculosis was microbiologically confirmed in 93 (53.4%). Yield on Ultra in first respiratory specimens was 39.1%. When the results of Ultra and mycobacterial culture on first respiratory specimens were combined, 47.1% (82/174) had microbiologically confirmed TB. Microcytic anaemia and pulmonary pathology were more common in confirmed TB. Of 81 children with microbiologically unconfirmed TB, 31 (38.3%) met a consensus definition of unconfirmed intrathoracic TB formulated by an international expert committee. In the subset of children (n=70) who were screened by Ultra on two sequential respiratory specimens, the incremental yield was 30.3%. When the results of Ultra and mycobacterial culture were combined the incremental yield in children who had 2 sequential respiratory specimens tested was 24.4% and 3.1% on Ultra and mycobacterial culture, respectively. Conclusion Ultra and/or mycobacterial culture on single respiratory specimens resulted in high microbiological yield. Ultra on second sequential respiratory specimens increased microbiological confirmation. The value of additional Ultra and/or mycobacterial culture testing in routine clinical practice requires further study.